2017
DOI: 10.1177/1203475417702994
|View full text |Cite
|
Sign up to set email alerts
|

Structured Expert Consensus on Actinic Keratosis: Treatment Algorithm Focusing on Daylight PDT

Abstract: Background: A practical and up-to-date consensus among experts is paramount to further improve patient care in actinic keratosis (AK). Objectives: To develop a structured consensus statement on the diagnosis, classification, and practical management of AK based on up-to-date information. Methods: A systematic review of AK clinical guidelines was conducted. This informed the preparation of a 3-round Delphi procedure followed by a consensus meeting, which combined the opinions of 16 clinical experts from 13 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 21 publications
(70 reference statements)
0
55
0
2
Order By: Relevance
“…However, high quality of cosmesis consistently observed in PDT studies for NMSC indications including AK, combined with increasing emphasis on patient choice over therapy, may see increased demand for topical PDT. A recent systematic review of AK clinical guidelines to construct a treatment algorithm positioned DL‐PDT a valuable option for patients with multiple AKs in small or large fields …”
Section: Current Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high quality of cosmesis consistently observed in PDT studies for NMSC indications including AK, combined with increasing emphasis on patient choice over therapy, may see increased demand for topical PDT. A recent systematic review of AK clinical guidelines to construct a treatment algorithm positioned DL‐PDT a valuable option for patients with multiple AKs in small or large fields …”
Section: Current Indicationsmentioning
confidence: 99%
“…A recent systematic review of AK clinical guidelines to construct a treatment algorithm positioned DL-PDT a valuable option for patients with multiple AKs in small or large fields. 99 Squamous cell carcinoma in situ (Bowen's disease)/invasive SCC Squamous cell carcinoma in situ (strength of recommendation A, quality of evidence 1) (approved indication)…”
Section: Current Indicationsmentioning
confidence: 99%
“…In the most recent expert consensus, dPDT has been positioned as a valuable option for patients with multiple AKs in small or large fields [25]. …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In a randomized, controlled trial in Europe, MAL DL‐PDT demonstrated similar efficacy, better tolerability with less pain and resulted in higher subject satisfaction compared to MAL c‐PDT . Furthermore, a structured expert consensus statement on AK recently rated MAL DL‐PDT as the preferred option for patients with multiple AKs on both small and large fields due to its efficacy and tolerability profile …”
Section: Introductionmentioning
confidence: 99%